2015
DOI: 10.1094/mpmi-08-15-0178-r
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Elevated CO2and Temperature on Pathogenicity Determinants and Virulence ofPotato virus X/Potyvirus-Associated Synergism

Abstract: Infections of plants by multiple viruses are common in nature and may result in synergisms in pathologies. Several environmental factors influence plant-virus interactions and act on virulence and host defense responses. Mixed viral infections may be more frequent under environmental conditions associated with global warming. Here, we address how changes in the two main parameters behind global warming, carbon dioxide concentrations ([CO₂]) and temperature, may affect virulence of Potato virus X (PVX)/potyviru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…Current climate prediction models indicate a gradual increase in CO 2 levels and an enhancement of the frequency and amplitude of heat and drought episodes (IPCC ). Moreover, changing environmental conditions may affect the incidence and severity of plant diseases and influence the further co‐evolution of plants and their pathogens (Eastburn et al ; Aguilar et al ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current climate prediction models indicate a gradual increase in CO 2 levels and an enhancement of the frequency and amplitude of heat and drought episodes (IPCC ). Moreover, changing environmental conditions may affect the incidence and severity of plant diseases and influence the further co‐evolution of plants and their pathogens (Eastburn et al ; Aguilar et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with single infections, co‐infection of Nicotiana benthamiana plants with PVX and Plum pox virus (PPV) resulted in increased virulence that led to necrotic symptoms in the newly emerging leaves. Furthermore, the expression of the P25 protein of PVX by a PPV vector was sufficient to induce an increase of PPV virulence that resembled that of the PPV/PVX synergistic interaction (Aguilar et al ,b).…”
Section: Introductionmentioning
confidence: 99%
“…These concerns have stimulated research on the effects on plants of multiple abiotic and pathogenic stresses (Malmstrom & Alexander, ). Recent research in this area has shown, for example, that increased CO 2 levels can affect the outcome of single or mixed virus infections (Aguilar et al, ). Another interesting phenomenon discovered from studies of stressed plants, is that virus‐infected plants can display increased resilience to cold and drought (Xu et al, ; Davis et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Baulcombe (University of Cambridge). The infectious cDNA clone of PVX carrying PPV HC-Pro (PVX-HC) sequences under the control of the PVX duplicated coat protein (CP) promoter was described before [24,33] . PPV expressing either PVX P25 ( PPV-P25) or GFP ( PPV-GFP) sequences in the viral polyprotein were described before [24].…”
Section: Binary Vector Constructsmentioning
confidence: 99%